The business plan for establishing hazelnut orchards in Azerbaijan. - Nazarov, Rufat (ADA University, 2023)
Hazelnuts provide a unique and delectable flavour to various meals, such as chocolate, spreads, and coffee. They contain several beneficial elements, such as protein and vitamins. Hazelnut oil serves as both a biofuel and a cooking oil. Moreover, hazelnut trees have several promising benefits for the surrounding ecology. Hazelnuts are grown in many countries, with Turkey, the United States, Italy, Spain, and Greece leading the way. Moreover, Azerbaijan is one of the world's major hazelnut producers. It is one of the most profitable agricultural exports for the country. Azerbaijan has a diverse hazelnut farming industry that yields a variety of cultivars. Ashrafli, Ghalib, Ganja, and Atababa have a distinctive flavour and 68.22% oil; Topgara and Sachagly have enormous kernel diameters and contain 50% oil. Atababa is the most extensively grown cultivar in Azerbaijan, accounting for more than 75% of total output. This type is popular among consumers because of its mild, exotic flavour and vibrant colour. Azerbaijan has grown 52 thousand tons of in-shell hazelnut and succeeded in keeping its third place in the world with a 6% share after Turkey (58%) and Italy (15%) in 2018. (Nut Soil, 2020) Considering the recent rise in the hazelnut industry in Azerbaijan, I decided to investigate the potential of creating a hazelnut orchard. To set up an orchard, you need to clear the land, put in a drip irrigation system, store fertiliser, choose high-yielding cultivars, and make water treatment systems. We are committed to employing devoted professionals that can quickly adjust to industry, market, and client preferences changes. Our long-term objective is to become Azerbaijan's leading producer and exporter of hazelnuts. To meet our company's objectives, we have built efficient operational procedures. In the "Introduction" section of my business plan, I presented a historical framework for the industry, an analysis of the market's current situation, possible development areas, and our recommended strategy for putting the firm into action. In the second section, "Company Description," I outlined the company's desired description, including its vision, mission, and core values, which would set it apart from the competitors. After assessing suitable places for a hazelnut garden and discussing how to build the facility, I provided information about the wide variety of hazelnut varieties and classifications that may be produced and exported to various countries worldwide. Also, I discussed my intentions for the firm's medium- and long-term growth. While developing the mentioned business plan, I considered the ethical and legal problems that may arise from operating this company. In the third "Market and Competitors Analysis" section of this business plan, several analyses, such as PESTEL, Porter's five forces, SWOT, VRIO, and the business model CANVAS, will be discussed. In addition, I determined customer expectations in this industry and market, which I believed was crucial to the success of this business. With the introduction of new technology, the utilisation of advanced agricultural knowledge and skills by small and medium sized farmers to improve hazelnut quality, and the construction of storage facilities, the market is anticipated to increase substantially. In the fourth part, under "Organization and Management," I detailed our management philosophy, human resource procedures, and organisational structure. We anticipate beginning with a modest staff once the company is operational. Most of the work at the facilities will be performed by the management, those who operate the machines, and the labour force. A healthy work atmosphere is crucial to the growth of our organisation. In this respect, I propose his thoughts on the ideal workplace and the organisation's future operations. Taking the branding and marketing plan into account, we will set the brand's parameters. All of these elements contribute to clients' first perception of the firm. The financial estimates and analysis in the fifth part of the business plan are one of the most critical parts. It is essential to assess if it is viable to begin the business and how it can be funded, whether investors would be interested, and whether the company can be financially managed effectively. I computed the total start-up charges and listed each expense. Projections predict that 497,945 AZN will be required. I intend to fund the project through shareholder equity. Given that the company's fourth year of operation should generate 383,353 AZN in revenue, this aim seems reasonable. Lastly, I discussed potential threats to the organisation and how we aim to prevent them. Every business must take into account the possibility of bankruptcy. Having a prepared contingency plan may aid company owners in weathering any storm. Investors will desire an exit plan in the scenario in which the business fails, or the owner decides to quit. These strategies will be discussed in the last section of the detailed plan.
Keywords: Hazelnut industry -- Azerbaijan; Hazelnuts -- Cultivation; Business planning -- Agricultural industries; Business